(untitled) (American Journal of Islam and Society, 2006)
This article investigates medieval Muslim literature on the study of non-Islamic religions through the writings of al-Biruni and al-Shahrastani in their dealing with Hind (India) and the nomenclature of world religions. I focus on their perceptions of monotheism and polytheism. My findings show that they used different approaches, categories, and classification models of world religious traditions in general, and of Hind’s religious traditions in particular. Al-Biruni classifies Indian religions according to the religious outlooks found in Hindu texts or sayings of Hindu philosophers/theologians and in the attitudes of ordinary people in a popular context. Al-Shahrastani categorizes the divisions and subdivisions of Hindu beliefs and practices according to types of “idol worshippers.” This article points out that they dealt with some conceptual issues in their presentations, such as “religious representation,” “intermediaries,” and “anthropomorphism.”